Machine Learning Algorithms for Diabetes Prediction: A Review Paper - Al-Sideiri A.; Cob Z.B.C.; Drus S.B.M. (Association for Computing Machinery, 2023)
Computer aided diagnosis; Data mining; Learning systems; Patient treatment; Predictive analytics; Robotics; Support vector machines; Data mining algorithm; Diabetes mellitus; Early diagnosis; Knowledge accumulation; Literature reviews; Prediction techniques; Review papers; Support vector machine algorithm; Learning algorithms